Origin, Distribution, Classification and Varieties of Sweet Cornmeal - Kholmamatovich, Khurramov Ulugbek; qizi, Sharipova Shokhsanam Shukhrat (American Journal of Biodiversity, 2025)
Sweet corn is an early ripening vegetable and is a promising vegetable crop for morning and evening planting periods. Sweet corn is recommended for planting, growing from seedlings and seeds in the morning and evening, on farms, landowners. The article provides brief information on the origin, distribution, classification and varieties of sweet corn.